Pendekatan Humanistik dalam PAI untuk Menumbuhkan Sikap Toleransi Beragama: Studi Lapangan di SMPN 1 Cireunghas Kabupaten Sukabumi - Ridhwanullah, Fadhlan; Nugraha, Mulyawan Safwandy (JIPENDIKA : Jurnal Inovasi Pembelajaran dan Pendidikan, 2026)
This study aims to examine the implementation of a humanistic approach in Islamic Religious Education (IRE) learning and its role in fostering religious tolerance among students at SMPN 1 Cireunghas, Sukabumi Regency. This research employed a qualitative approach with a field research design. The research subjects included Islamic Religious Education teachers, the school principal or vice principal for curriculum affairs, and students as supporting informants. Data were collected through in-depth interviews, non-participant observations, and documentation studies. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the humanistic approach in IRE learning was implemented through dialogical learning processes, respect for diverse opinions, and the integration of learning materials with students’ real-life contexts. This approach plays a significant role in fostering students’ religious tolerance, as reflected in attitudes of mutual respect, cooperation, and empathy among students. Supporting factors include school policy support and teachers’ openness, while inhibiting factors include limited instructional time and diverse student characteristics.